Advancements and challenges in protein purification techniques for denitrifying enzymes: A path to effective nitrogen removal and reduced N2O emissions - Liu, Lingxiu; Li, Anhang; Shi, Changjie; Hrynsphan, Dzmitry; Tatsiana, Savitskaya; Wang, Zeyu; Chen, Jun (Critical reviews in environmental science and technology, 2024)
The biological denitrification process is crucial for removing nitrogen and reducing nitrous oxide (N 2 O) emissions. To investigate the mechanism of action of key enzymes in the denitrification process, it is necessary to analyze the protein structure, active site, and conformational changes of denitrifying enzymes. X-ray crystallography, nuclear magnetic resonance (NMR), and cryogenic electron microscopy (Cryo-EM), as well as spectroscopic analyses such as Raman resonance and UV-vis, have been used to study the structure of denitrifying enzymes. However, practical application is limited by protein folding and assembly, as well as issues of purity, concentration, and homogeneity. This review summarizes the biochemical properties of the four denitrifying enzymes and typical purification methods. Additionally, this review emphasizes important factors to consider during protein expression, crude extract, and chromatographic purification. It also provides insight into the future development of protein purification methods for denitrifying enzymes. This review aims to bridge the gap between the complex biochemical process of denitrifying enzymes and the technical intricacies of protein purification, with the ultimate goal of reducing N 2 O emissions in ecosystems.